The relationship between women leadership Styles and organizational health - Al-Saati, Faten Zuhair Ahmed; Al-Anqari, Ghada AbdelRahman (Journal of Economic, Administrative and Legal Sciences, 2024)
This research aims to know women leadership style at King Saud University, the facts of organizational health, and the relationship between them. The research population consists of (400) female administrative employees in King Saud University. The researcher relied on the Survey methodology and the questionnaire as a tool for data collection. The most important results of the research are summarized in the idea that democratic leadership style is the dominant women leadership styles and the most applied and contributing in order to achieve organizational health, as it had an arithmetic average of (3.81) and a standard deviation of (0.95). The reality of organizational health among women administrative employees at King Saud University was high with an arithmetic average of (3.77) and a standard deviation of (0.68). It also shows a direct relationship between the democratic leadership style and organizational health with a correlation coefficient of (0.690) at a significance level of (0.00). Also, the results showed that there is no relationship between the autocratic leadership style and the Free-rein leadership with organizational health. The most important recommendations are the nomination and selection of women leadership according to criteria that pay attention to the dimensions of organizational health, with attention to providing them with financial and emotional incentives, in order to continue applying the appropriate leadership style to enhance the level of organizational health in the university. Work to create a balance between the productivity and achievement of administrative female employees with their salaries, by evaluating performance during specific.